The Effectiveness of Al-Qur'an Reading Culture to Improve Character Education and Student Learning Motivation - Wiwin Agustin; Suparman Suparman; Ayuning Atmasari (Universitas Pahlawan Tuanku Tambusai, 2022)
The author found that some students of SMAN 3 Sumbawa Besar have less commendable behavior and lack of enthusiasm in learning so that students' self-development is needed to improve character education and learning motivation, namely with the culture of reading the Qur'an. This study aims to determine the implementation of Qur'an reading culture in improving character education and student learning motivation, and to analyze the effectiveness of the implementation of Qur'an reading culture on character education and student learning motivation. The type of research used is descriptive quantitative with data collection procedures through questionnaires and documentation, and data are analyzed with normality tests, multicholinearity tests, heterochedasticity tests, multiple regression tests. The results showed a signification value of 0.016 < 0.05 and a Fhitung value of 4.434 > Ftabel means that the effectiveness of the culture of reading the Qur'an can increase character education and student learning motivation. So it can be concluded that the culture of reading the Qur'an is effective in increasing character education and student learning motivation at SMAN 3 Sumbawa Besar.